2012
DOI: 10.1590/s0004-282x2012000100009
|View full text |Cite
|
Sign up to set email alerts
|

Devising and validating a headache diary in a series of patients with chronic daily headache from Colombia

Abstract: Objective: To devise and test the reliability and validity of a brief headache diary in a series of Colombian patients with chronic daily headache. Methods: The study was designed in five stages: selection of domains (group of patients and experts); initial devising of the items (writing group); identification of non-understandable items (n=20); assessment of internal consistency (n=100); assessment of validity and assessment of sensitivity to change during seven consecutive days (n=25, 175 observations). Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 16 publications
(27 reference statements)
0
13
0
1
Order By: Relevance
“…Fourteen studies fulfilling the eligibility criteria were identified. [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] Reasons for exclusion included non-pain populations (n = 8), non-chronic populations (n = 5), no psychometric comparisons (n = 5), not EMA (n = 5), and conference abstracts without data (n = 6). All included studies were written in English.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fourteen studies fulfilling the eligibility criteria were identified. [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] Reasons for exclusion included non-pain populations (n = 8), non-chronic populations (n = 5), no psychometric comparisons (n = 5), not EMA (n = 5), and conference abstracts without data (n = 6). All included studies were written in English.…”
Section: Resultsmentioning
confidence: 99%
“…39 The chronic pain conditions studied were osteoarthritis, rheumatoid arthritis, lupus, fibromyalgia, spinal cord injury, low back pain, generalized musculoskeletal pain, irritable bowel syndrome, and headache. [38][39][40][41][42][43][44][46][47][48][49][50][51][52] Ethnicity was not consistently reported; however, samples were mainly made up of Caucasian participants in studies that reported ethnicity details. Three studies were made up of a majority of Colombian 51 and Spanish 50 and 1 of Dutch 43 participants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Modificación de la metodología de trabajo: creación de un protocolo de atención al usuario con cefalea; aumento de 15 minutos en el tiempo dedicado a estos pacientes; dedicar un tiempo a la explicación de cómo realizar los ejercicios domiciliarios; entregar el primer día el cuestionario HIT-6 a cada paciente, el diario de cefalea 22 , la tabla de ejercicios, y la encuesta MedRisk 23 , además de acordar realizar sesiones clínicas cada 3 meses.…”
Section: Materials Y Métodosunclassified